Ocorrência de bactérias diazotróficas em cactáceas nativas do semiárido e seus efeitos no crescimento de mudas de Mandacaru - Lima, José Vinícius Leite (2013)
The presence of nitrogen-fixing bacteria has been observed in various plant species, including legumes, grasses, and fruit plants. It has been hypothesized that the cactus from semiarid region naturally establishes association with endophytic bacteria and take advantages from plant-bacteria interaction in the initial growth phase. This study aimed to isolate and characterize diazotrophic from cactus in semiarid and evaluate their contribution on the growth of Mandacaru seedlings. The survey of occurrence of diazotrophs was held in December 2011, collecting samples from roots and aerial parts of Mandacaru (Cereus jamacaru) and Coroa-de-frade (Melocactus zehntneri) at the Ecological Station of Aiuaba, state of Ceará, Brazil. The presence of endophytic bacteria was confirmed in native cacti and bacterial strains characterized by the physiology of growth on artificial medium, on condition of biological nitrogen fixation. Representative strains from homogeneous bacterial groups were used to inoculate Mandacaru seedlings. After six months of growing in greenhouse, the Mandacaru seedlings showed similar growth independently of bacterial inoculation. All bacteria obtained cacti showed ability showed ability to solubilize inorganic phosphate in medium Pikoskaya. The endophytes obtained differ in growth condition under nitrogen fixation and by using different carbon sources. The seven bacterial strains tested did not affect significantly the initial growth of Mandacaru in substrates with rice hulls partially burned, vermiculite and humus.